Sex Disparities in the Self-Evaluation of Subthalamic Deep Brain Stimulation Effects on Mood and Personality in Parkinson's Disease Patients - Dietrich, Amelie D.; Koeppen, Johannes A.; Buhmann, Carsten; Pötter-Nerger, Monika; Pinnschmidt, Hans O.; Oehlwein, Christian; Oehlwein, Marita; Mittmann, Katrin; Gerloff, Christian; Engel, Andreas K.; Westphal, Manfred; Schaper, Miriam; et al. (Frontiers in Neurology, 2020)
Changes in personality are one of the main concerns Parkinson’s disease (PD) patients raise when facing the decision to undergo neurosurgery for deep brain stimulation (DBS) of the subthalamic nucleus (STN). While clinical instruments for monitoring functional changes following DBS surgery are well established in the daily therapeutic routine, personality issues are far less systematically encompassed. Moreover, while sex disparities in the outcomes of STN-DBS therapy have been reported, little is known about the different effects that DBS treatment may have on mood and personality traits in female and male patients. To this aim, the effect of STN-DBS on personality traits was assessed in 46 PD patients (12 women and 34 men) by means of the Freiburg Personality Inventory. The Becks Depression Inventory (BDI-I) and the Parkinson’s Disease Questionnaire were used to evaluate patients’ level of depression and quality of life (QoL). Patients completed the questionnaires a few days before, within the first year, and two years after surgery. The 12 personality traits defined by the FPI-R questionnaire did not change significantly after STN-DBS surgery (p = 0.198). Women declared higher depression scores through all study stages (p = 0.009), but also showed a stronger QoL amelioration after surgery than male patients (p = 0.022). The BDI-I scores of female patients clearly correlated with their levodopa equivalent daily dose (LEDD; r = 0.621, p = 0.008). Remarkably, in both male and female patients, higher pre-operative LEDDs were related to worse post-operative QoL scores (p = 0.034). These results mitigate the concerns about systematic personality changes due to STN-DBS treatment in PD patients and encourage an early DBS approach, before severe levodopa-induced sequelae may irreparably compromise the patients’ QoL. In the future, more focus should lie on sex-related effects, since female patients seem to profit more than male patients from STN-DBS, in terms of reduced depressive symptoms associated with a reduction of the LEDD and amelioration of QoL. These aspects may help to redress the sex imbalance in PD patients treated with DBS, given that women are still strongly under-represented.